Ethnomethodological Insights into Hybrid Contract Practices in Islamic Accounting - Annurria, Wanti; Dahlifah, Dahlifah; Mais, Rimi Gusliana (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
This study aims to explore the implementation of Sharia accounting for hybrid contract financing at PT Bank Syariah Indonesia Tbk., where several contracts are not yet regulated under current Sharia Accounting Standards. The focus of this research is to identify how these hybrid contracts align with Sharia principles and the existing regulatory framework while assessing the practical challenges faced by Islamic financial institutions. The primary data sources include direct observations and in-depth interviews with informants, specifically employees of PT Bank Syariah Indonesia Tbk., who provide insights into the operationalization of Sharia accounting in practice. This research adopts a qualitative approach with an interpretive paradigm, utilizing the ethnomethodology method to conduct an in-depth analysis of indexicality, reflexivity, and accountability within the accounting processes. The findings reveal that the application of Sharia accounting in hybrid contract financing at PT Bank Syariah Indonesia Tbk. represents a form of innovation that consistently aligns with regulations, Sharia principles, and Sharia accounting standards. Despite the absence of comprehensive standards, the bank effectively adapts existing guidelines to manage these hybrid contracts realistically. To support the ongoing development of Islamic banking in Indonesia, it is imperative for regulators and standards boards to establish detailed rules and guidelines for Sharia accounting in hybrid contract financing, ensuring uniformity and transparency across the industry.